Prediction of noise radiation on cylinder head - Awang, Muhamad Khairudin (2004)
Noise radiation analysis of an engine's component can be implemented through several methods such as theoretical calculations, experimental and simulation. The use of finite element method integrated with boundary element method based computer software in engineering field has shown growing interest due to shorter duration of analysis and easy to use. In this analysis, observation of vibration characteristic for two-stroke engine's cylinder head is carried out. Initially, finite elements are used to create the engine's cylinder head model. Data gained from modal analysis is used for prediction of noise radiation from cylinder head surfaces. At this stage, acoustic boundary element model is preferred instead of finite element model. Finally, the results of this study can be used for further analysis in designing of two-stroke gasoline engine.